Use of Microorganisms as Bioindicators for Detection of Heavy Metals - Ahmad, Fazuriana (2006)
In this study, soil bacteria were isolated and were then screened for their sensitivity to heavy metals. This study employs the tetrazolium dye MTT (3-(4,5-demethyl-thiazol-2-yl)-2,5-diphenyltetrazolium bromide) where bacteria reduced the dye, causing the dye to precipitate and to become intensely coloured. In the presence of heavy metals, the reduction will be inhibited and become colourless. A total of 250 bacterial isolates were successfully obtained from 10 different locations in Peninsular Malaysia which were then screened with six selected heavy metals in the presence of common divalent cations such as calcium and magnesium at the highest concentration of 25 mg/L and 50mg/L respectively using a MTT assay. An isolate designated as isolate SC27 at 8 hours growth and isolate S8 at 12 hours growth were found to be most sensitive to mercury and silver respectively. The IC50 (50% inhibitory concentration) of mercury and silver are 0.2698 mg/L and 0.073 mg/L respectively after data was analyzed using the Graphpad Prism™ version 4.0 software. The assay was found to be unaffected by interference from other tested xenobiotics. Preliminary field study tests showed the ability of these two bacterial isolates to detect mercury and silver after comparison with AAS analysis. Isolate SC27 was identified as Uncultured bacterium strain Dr.Y13 (DQ 226214) which is related to Enterobacter sp. using Microbact™ kit and was confirmed using 16S rRNA gene analysis while isolate S8 was identified as Serratia sp. with 90.79 % similarity using the Microbact™ kit.